Identification of biotransformation products of disperse dyes with rat liver microsomes by LC-MS/MS and theoretical studies with DNA: Structure-mutagenicity relationship using Salmonella/microsome assay - Franco, Jefferson Honorio [UNESP]; Silva, Bianca F. da [UNESP]; Oliveira, Regina V.; Meireles, Gabriela; de Oliveira, Danielle Palma; Castro, Alexandre A. de; Ramalho, Teodorico C.; Zanoni, Maria V.B. [UNESP] (Elsevier, 2018)
Azo dyes are known as a group of substances with DNA damage potential that depend on the nature and number of azo groups connected to aromatic rings (benzene and naphthalene), chemical properties, e.g. solubility and reactive functional groups, which significantly affect their toxicological and ecological risks. In this paper, we used in vitro models to evaluate the metabolism of selected textile dyes: Disperse Red 73 (DR 73), Disperse Red 78 (DR 78) and Disperse Red 167 (DR 167). To evaluate the mutagenic potential of the textile dyes, the Salmonella mutagenicity assay (Ames test) with strains TA 98 and TA 100 in the presence and absence of the exogenous metabolic system (S9) was used. DR73 was considered the most mutagenic compound, inducing both replacement base pairs (TA 100) and also changing frameshift (TA 98) mutations that are reduced in the presence of the S9 mixture. Furthermore, we used rat liver microsomes in the same experimental conditions of the S9 mixture to metabolize the dyes and the resultant solutions were analyzed using a liquid chromatography coupled to a quadrupole linear ion trap mass spectrometry (LC-MS/MS) to investigate the metabolites formed by the in vitro biotransformation. Based on this experiment, we detected and identified two biotransformation products for each textile dye substrate analyzed. Furthermore, to evaluate the interaction and reactivity of these compounds with DNA, theoretical calculations were also carried out. The results showed that the chemical reaction occurred preferentially at the azo group and the nitro group, indicating that there was a reduction in these groups by the CYP P450 enzymes presented in the rat microsomal medium. Our results clearly demonstrated that the reduction of these dyes by biological systems is a great environmental concern due to increased genotoxicity for the body of living beings, especially for humans.
Keywords: Ames Test; Computational study; In vitro biotransformation; Mass spectrometry; Rat liver microsome; Textile dye